PEMBEBANAN HAK TANGGUNGAN DALAM PERJANJIAN KREDIT BANK DI KABUPATEN BADUNG - Lilik Purnama Dewi, Ni Ketut; Wiryawan, I Wayan; Rudy, Dewa Gede (Kertha Semaya : Journal Ilmu Hukum, 2013)
Bank is one of effort body which sharing of vital importance in Stateeconomics, because besides as place to save money the, bank also represent thefund dealer in the form of credit. In credit needed by the existence ofdone/conducted by later guarantee of encumbering of guarantee object to fastenthe bank with the debitor with the installation of Responsibility Rightsdone/conducted by Notary. In article entitling Encumbering of ResponsibilityRights of In Agreement of Bank Credit in this Regency Badung will studyproblems that is What will be legal consequences to letter of attorney burden theresponsibility rights which is not continued to Deed of Gift of ResponsibilityRights ( APHT) in the case of the happening of debt. Method used by is empiricthat is research which is pursuant to in the situation or fact and also interviewwith the notary of regency Badung. From interview done/conducted to be got byconclusion that legal consequences generated by if SKMHT is not continued withthe installation APHT is cancelation for the shake of law.
Keywords: Bank, Notary, Law